"Where Did This [PrEP] Come From?" African American Mother/Daughter Perceptions Related to Adolescent Preexposure Prophylaxis (PrEP) Utilization and Clinical Trial Participation. (April 2018) - Fletcher, Faith E.; Fisher, Celia; Buchberg, Meredith K.; Floyd, Brenikki; Hotton, Anna; Ehioba, Angelica; Donenberg, Geri
Despite the demonstrated effectiveness of preexposure prophylaxis (PrEP) to reduce incident HIV infections, PrEP's potential as an HIV prevention strategy for adolescent populations is unknown. This study assessed perceptions of adolescent PrEP use and clinical trial participation among African American women and their adolescent daughters. We conducted focus group discussions with 15 African American mother/daughter pairs ( N = 30). Findings suggest a general lack of PrEP awareness, favorable attitudes toward adolescent PrEP use, altruistic attitudes regarding research participation among daughters, and less favorable attitudes toward adolescent clinical trial participation among mothers. Study findings have the potential to inform strategies that provide equitable access to HIV scientific advances among African American women and girls and promote informed parent–child research decision making.